(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Fagonia arabica, commonly known as “Dhamasa,” is revered in Ayurveda for its multifaceted medicinal properties. Widely used in South Asia and the Middle East, it has been a staple in traditional medicine systems such as Ayurveda and Unani. In this review, a comprehensive search was performed using various scientific databases, including PubMed, Scopus, and Google Scholar. Keywords such as “Fagonia Arabica Linn,” “therapeutic potential,” “medicinal properties,” and “phytochemical constituents” were employed to ensure a comprehensive retrieval of relevant literature. The extensive literature analysis showed that F. arabica has been long utilized in Middle Eastern and South Asian populations for the treatment of a variety of illnesses, as well as in Ayurvedic and Unani medicine. The plant exhibits a rich history of ethnopharmacological uses across diverse geographic regions. From being a diuretic in India to treating skin diseases and wounds, F. arabica’s applications are varied. In Pakistan, it is employed for treating hepatitis, and fever, and even serves as an immunomodulator. The plant’s extensive use encompasses regions such as Libya and Saudi Arabia, where it is used as an antihypertensive, antibacterial, and antioxidant. The chemical composition of F. arabica includes flavonoids, triterpenoidal glycosides, and saponins. These compounds contribute to the plant’s antioxidant activity, making it a potent natural remedy. F. arabica has a spectrum of pharmacological activities, including anti-inflammatory, anti-allergic, neuroprotective, and cytotoxic activity. The plant’s role as an immunomodulator, deobstruent, analgesic, neuroprotective, and hepatoprotective adds to its pharmacological significance. F. arabica stands as a medicinal marvel with a rich history of traditional use and a promising array of pharmacological benefits